Influência da instrução na correção do valgo dinâmico do joelho e na ativação muscular do glúteo médio em adolescentes com dor patelofemoral - Souza, Gabriela dos Santos de (2019)
Patellofemoral pain (PF) is commonly found in the adolescent population and this condition is related to the desertion of sports and physical activity. Contrary to what has thought the painful condition presents with symptoms persisting for years and beyond adolescence. Adduction and excessive internal rotation of the hip during weight-bearing activities are related to dynamic knee valgus (DKV). This abnormality in movement control causes overload and stress of the patellofemoral joint, generating pain and decreased functionality. Recently it has been theorized that changes proximal activation and strength of the hip muscles, such as the gluteus, may be related to compensatory biomechanical changes leading to a medial collapse of the knee. Many studies have verified the influence of muscle-strengthening programs on DKV in individuals with PF, others have bet on programs with added motor control exercises. However, few studies have looked at the immediate influence of a brief instruction for awareness and correction of motor gesture using feedbacks. The objective of the study was to analyze the effectiveness of instruction in the correction of DKV during a functional task and on Gméd muscle activity in adolescents with PF. Fifteen female adolescents participated in the study, aged 13 to 17 years, divided into Patellofemoral Pain Group (GPF=9) and Control Group (CG=6). Surface electromyography (EMG) measured the electrical activity of the Gméd muscle and from the kinematics, it was determined the frontal plane projection angle (FPPA) during Lateral Step down (LSD) functional test, before and after receiving DKV correction instruction. The results for the post-instruction condition were a decrease in FPPA in GPF (p <0.001), similar to the adolescents without PF and DKV, from the CG (p =0.676). Gméd muscle activation was already higher in GPF compared to the CG (p <0.024). It was evidenced, after the instruction for DKV correction, an increase of Gméd muscle activation (p <0.044). Changes in muscle activation patterns may represent a strategy of possible compensations in participants with PF. It is suggested that the greater activation of the Gméd muscle observed since the pretest in participants with PF, and 50% of the lower limbs, the post-test, it may be due to weaker hip muscles. The instruction was able to reduce medial knee collapse by 83% of the lower limbs analyzed and the Gméd muscle may have been the neuromuscular strategy used by half of the participants. We recommend that future studies investigate the involvement of other muscles, because the DKV is an extremely complex and challenging change of motion. It is concluded that a brief instruction was able to correct the dynamic knee valgus in adolescents with patellofemoral pain.